Existe Alteração em Marcadores Inflamatórios em Estudantes de Medicina após Participação em Programa Mente-Corpo? - Catarucci, Fernanda Martin; Bruno, Vânia Hercília Talarico; Habimorad, Pedro Henrique Leonetti; Beteto, Ivan Da Silva; Andrews, Susan; Sandrim, Valéria Cristina; Burdmann, Emmanuel A.; Patrício, Karina Pavão (Associação Brasileira de Educação Médica, 2019)
ABSTRACTIntroductionMedical students are exposed to high stress levels, triggered by having to deal with their illness and death of their patients, extensive workloads, sleep deprivation, competition, having to fulfil demanding duties, responsibility, and fear of making mistakes, among other factors. Some techniques and practices, such as meditation, are used in medical schools to help manage and reduce stress. Stress can activate components of the inflammatory system, triggering a series of pathologies. The disorders caused by stress can be measured by means of serological markers, with biological markers being the main ones used. Objective. To evaluate the effects of a program of mind-body practices, Reduction of Stress and Development of Empathy in Medicine (REDEMED ©), on pro- and anti-inflammatory markers of medical students.MethodologyThis is a quasi-experimental study, composed of 86 students: 44 in the intervention group, who participated in the REDMED© program with eight-weekly meetings that included meditation techniques and exercises of interpersonal experiences, and 42 students in the control group. Before and after the course, blood was collected from both groups for analysis of the markers: C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL06) and interleukin-10 (IL10).ResultNo statistically significant changes were observed in the proinflammatory cytokines CRP, TNF-α and IL06. However, IL-10, an anti-inflammatory cytokine, showed a positive and statistically significant variation (p: 0.009). It has been used in studies with integrative and complementary practices to demonstrate its benefits.ConclusionThe REDEMED© program seems to benefit medical students through inflammatory modulation and as a group that provides a forum to share their stress and receive coaching in coping strategies. This study, even though it did not find a statistically significant difference in the markers studied, with the exception of IL10, raises the important theme of the high levels of stress that medical students experience, and the need for medical schools to take greater care of their students, addressing stress in order better manage it in their own lives.

RESUMOIntroduçãoEstudantes do curso de Medicina estão expostos a carga elevada de estresse, desencadeada por terem que lidar com adoecimento e morte dos pacientes, extensa carga horária, privação de sono, competitividade, cobrança, responsabilidade e medo de errar, entre outros fatores. Algumas técnicas e práticas como a meditação têm sido utilizadas para auxiliar no manejo e redução de estresse, já sendo utilizadas em escolas médicas. O estresse pode ativar componentes do sistema inflamatório, desencadeando uma série de doenças. As desordens causadas pelo estresse podem ser mensuradas por meio de marcadores sorológicos, sendo que os biológicos são os principais utilizados.ObjetivoAvaliar os efeitos de um programa de práticas mente-corpo, Redução de Estresse e Desenvolvimento da Empatia na Medicina (Redemed©), nos níveis dos marcadores pró- e anti-inflamatórios de estudantes de medicina.MetodologiaTrata-se de um estudo quase-experimental, composto por 86 estudantes, sendo 44 do grupo intervenção, que participaram do programa Redemed© com oito encontros semanais, englobando técnicas de meditação e exercícios de vivências interpessoais, e 42 estudantes do grupo controle. Ambos os grupos, antes e após o curso, coletaram sangue para análise dos marcadores: proteína C reativa (PCR), fator de necrose tumoral-alfa (TNF-alfa), interleucina 06 (IL06) e interleucina 10 (IL10).ResultadoNeste estudo, não foi observada alteração estatisticamente significativa nas citocinas pró-inflamatórias: PCR, TNF-α e IL06. No entanto, a IL-10, que é uma citocina anti-inflamatória, apresentou uma variação positiva e estatisticamente significativa (p: 0,009). Ela tem sido utilizada em estudos com práticas integrativas e complementares a fim de demonstrar seus benefícios.ConclusãoO programa Redemed© parece beneficiar os estudantes de Medicina por meio da modulação inflamatória e como grupo de acolhimento no qual eles puderam compartilhar seu estresse e treinar estratégias de enfrentamento. Este estudo, mesmo não tendo encontrado diferença estatística significativa nos marcadores pesquisados, com exceção da IL10, traz à tona este tema importante do grande estresse vivenciado por estudantes de Medicina e a necessidade de as escolas médicas terem maior cuidado com seus alunos, acolhendo e trabalhando o estresse desses estudantes de forma a reduzir e gerenciar melhor este fator de adoecimento em suas vidas.
Is There Any Change in Inflammatory Markers in Medical Students after Participating in a Mind-Body Program?
Keywords: Medical education; Medical students; Stress; Inflammatory markers; Meditation; Educação médica; Estudantes de medicina; Estresse; Marcadores inflamatórios; Meditação